2021
DOI: 10.4209/aaqr.200573
|View full text |Cite
|
Sign up to set email alerts
|

Source Quantification of PM10 and PM2.5 Using Iron Tracer Mass Balance in a Seoul Subway Station, South Korea

Abstract: In this study, we measured simultaneously particle matter (PM10 and PM2.5) mass and their heavy metal concentrations for three days at a Seoul subway station (outdoor, concourse, platform, and tunnel) to investigate airborne PM flows. The average PM10 concentration were 59 µg m-3 , 37 µg m-3 , 111 µg m-3 and 369 µg m-3 ; PM2.5 concentration were 43 µg m-3 , 28 µg m-3 , 58 µg m-3 and 132 µg m-3 in outdoor, concourse, platform and tunnel, respectively. Although PM temporal variations were highly correlated betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These tests took place under excellent outdoor air conditions that did not worsen PM 2.5 pollution in the subway stations, but station concentrations were still at high levels that cannot be ignored, most of which exceeded the WHO standard. Therefore, many scholars reported that there are PM 2.5 sources in subway stations, such as friction between steel rails and wheels, metal brake pads, and ventilation systems (Son et al 2021 ; Zhang et al 2011 ). The dilution effect of clean outdoor air on polluted air in subway stations is limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests took place under excellent outdoor air conditions that did not worsen PM 2.5 pollution in the subway stations, but station concentrations were still at high levels that cannot be ignored, most of which exceeded the WHO standard. Therefore, many scholars reported that there are PM 2.5 sources in subway stations, such as friction between steel rails and wheels, metal brake pads, and ventilation systems (Son et al 2021 ; Zhang et al 2011 ). The dilution effect of clean outdoor air on polluted air in subway stations is limited.…”
Section: Resultsmentioning
confidence: 99%
“…These semi-closed internal spaces are connected to the atmospheric environment mainly through entrance/exit channels, tunnel air shafts, and ventilation systems, which are not conducive to PM 2.5 diffusion in stations. Test studies in many cities, including Philadelphia (Shakya et al 2020 ), Lisbon (Correia et al 2020 ), Seoul (Son et al 2021 ), Naples (Carteni et al 2020 ), Boston, and Washington DC (Luglio et al 2021 ), have shown that PM 2.5 concentrations in subway stations were significantly higher than outdoors. In many subway stations, PM 2.5 concentrations exceed the indoor air quality standard.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has already studied the presence of PM2.5 and PM10 in subway stations [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The geographical locations covered by this research are shown in Table 1 .…”
Section: Introductionmentioning
confidence: 99%